Guidelines for Improving the Efficiency of Ring Jewelry Production in the Design and Metal Casting Processes - Pudanpha, Aphisith (Rattanakosin Journal of Social Sciences and Humanities, 2023)
This research is an experimental and qualitative research on an approach to increase the production efficiency of ring work jewelry in the design and casting processes. The objectives of the research are 1) to study and analyze the efficiency of ring work jewelry production, 2) to explore methods for reducing waste in the production processes of ring jewelry, and 3) to investigate problems and preventive measures in the production of ring jewelry. The sample group used in this research consists of 180 rings with production issues, which were selected for the study. The research was conducted using actual working procedures and machinery, along with the incorporation of modern technologies. The results of the study revealed that factors affecting the quality of rings range from the design process to the casting process. Issues with machinery and production processes were identified, including problems with porosity, air bubbles, cracks, and incomplete casting. Each process required development and improvement to achieve better results. Establishing standards for each process is crucial to provide valuable reference information for future developments.